The Effect of Location, Price, and Promotion on Investor Interest in the Development Area of PT. Industrial Estate of Makassar - Arief Fajar Kurniawan; Siti Haerani; Nurdjanah Hamid (Magister Management, Hasanuddin University, 2021)
The purpose of this research is to analyze the effect of location, price, and promotion on investment interest in PT Industrial Estate of Makassar (Persero) located in Maros Regency. The study applied a quantitative process by statistical methods. The study use multiple regression analysis and classical assumptions were tested beforehand. The study collected the data through questionnaire distributions to 60 respondents of enterprise consumers. The results of the study found that a strategic location became the main attraction in the process of growing investor interest in the services offered in the development area of the company. Furthermore, the price offered by PT. Industrial Estate of Makassar (Persero) to investors can create investment interest because the price offered has a value in accordance with what will be obtained. Meanwhile, promotions that are not carried out on a massive scale become things that cannot affect investor interest, besides certain conditions where promotions do not affect interest because investors sometimes seek information directly before PT. Industrial Estate of Makassar (Persero) conducts promotions through the media.